THE USE OF «CLOUD COMPUTING» IS AT HIGHER SCHOOL - Arkhipova Т.Л.; Zaytseva Т.В. (Journal of Information Technologies in Education (ITE), 2014)
To improve the training process is necessary to use such powerful technologies, as ‘cloud computing’. Supporting traditional training forms, it’s the new epoch of education development. It’s also economic, effective and flexible way to satisfy the needs of taught in new knowledge getting.‘Cloud computing’ is a dynamically scaled way to access external resources for computing as a service provided with the help of Internet. The user does not need any special knowledge about the ‘cloud’ infrastructure or the control skills of this ‘cloud technology’. This article discusses the uses of ‘cloud computing’ by the teachers of the department of Computer Science in Kherson State University to train future professionals. Teachers often use a mixed hybrid model of cloud computing which allows using state, public and private resources providing a major advantage for their deployment. Formation of knowledge and skills using modern resources including cloud computing is one of the most important components of professional competence of the future teacher in Computer Science and software engineer who is one of the main representatives of the list of information technology specialis